Evaluasi Keberhasilan Studi Mahasiswa Program Sinergi S1-S2 Institut Pertanian Bogor - Imas Fatimah; Eka Intan Kumala Putri; Utami Dyah Safitri (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This study aims to determine profile of fast track program based on the characteristics input and knowing the factors that influence academic achievement student of fast track program bachelor to master degree IPB. The method used in this study were descriptive analysis and classification and regression tree (CART). This research used primary and secondary data. Primary data were the result of interviews fast track program and secondary data were characteristic input fast track program. The results of the research study show student profile of fast track program dominated by female students, single, study program that have accreditation A, pass an English placement test and self-financing. The CART analysis finds two significant factors associated to student achievement. They were GPA score S1 and selection study program. Other factors are, based on interview result, motivation and commitment of the student in completing the study, type of research, as well as role and commitment of the supervisor in completing the study.Abstrak: Penelitian ini bertujuan menganalisis profil mahasiswa Program Sinergi S1-S2 IPB berdasarkan karakteristik input mahasiswa menggunakan analisis deskriptif. Selanjutnya, menganalisis faktor faktor yang memengaruhi keberhasilan studi mahasiswa menggunakan analisis Classification and Regression Tree (CART) Hasil penelitian menunjukkan bahwa profil mahasiswa Program Sinergi S1-S2 IPB ditinjau dari karakteristik input mahasiswa didominasi oleh mahasiswa perempuan, belum menikah, program studi S2 mempunyai akreditasi A, lulus placement test Bahasa Inggris dan sumber pembiayaan mandiri. Faktor-faktor yang berpengaruh terhadap keberhasilan studi mahasiswa Program Sinergi S1-S2 IPB menggunakan metode CART adalah IPK pendidikan S1 dan pilihan program studi S2. Motivasi dan komitmen mahasiswa dalam menyelesaikan studi, jenis penelitian mahasiswa dan peran dosen pembimbing dalam menyelesaikan studi mahasiswa merupakan faktor lain yang memengaruhi keberhasilan studi mahasiswa dan lulusan Program Sinergi S1-S2 IPB.